The Influence of Profitability and Leverage on Tax Avoidance in Manufacturing Companies Listed on the Indonesian Stock Exchange 2018 - 2020 - Nurrobani, Mohamad Rizqi (Moneta : Journal of Economics and Finance, 2023)
Tax is one of the largest revenues in the APBN, but when compared to the realization of the tax revenue target, it is still not appropriate. In this thesis the author indicates that this happened because there was resistance made by the taxpayer in the form of tax avoidance. This study aims to determine the magnitude of the influence of Profitability, and Leverage on Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020. The data used in this thesis is secondary data, namely financial statements obtained from the official website of the Indonesia Stock Exchange ( www.idx.com). Sampling by purposive sampling was obtained as many as 10 companies with a research time of 2018 - 2020. The analysis method used was the regression test method and used SPSS version 24 for data processing. The results of this study indicate that profitability partially has a significant positive effect on tax avoidance, partially leverage has a significant positive effect on tax avoidance. Profitability, and Leverage, simultaneously have an effect on tax avoidance.